Peran Aktivitas Fisik dan Sosiodemografis dalam Meningkatkan Kesejahteraan Lansia: Tinjauan Literatur - Candra, Adil; Rachmawati, Imami Nur; Rekawati, Etty (Universitas Faletehan, 2024)
The increasing population of the elderly presents new challenges concerning quality of life. The depiction of elderly physical activity is influenced by their level of well-being. This study aimed to examine the depiction of factors influencing physical activity and independence among the elderly, which impact optimal elderly quality of life. Three journal databases, namely Scopus, Science Direct, and ProQuest were utilized for the period spanning from 2002 to 2022. The search yielded six articles meeting the inclusion criteria. Findings from the literature review indicated that elderly physical activity is associated with various aspects of their well-being, such as prosperity, social relationships, physical and mental health. Socio-demographic factors, such as gender, age, assets, and income were also linked to the elderly's activity profiles. Another finding suggested the necessity for the development and implementation of technology in the planning and management of recreational and health activities for the elderly. It can enhance various aspects of elderly well-being, including physical work capacity, emotional status, somatic health, and cognitive function. In conclusion, physical activity plays a crucial role in enhancing overall elderly well-being, while socio-demographic factors and social environments also significantly influence elderly activity profiles and well-being.